Synthesis of α‐Keto‐1, 2, 3‐triazoles Through Copper Iodide Catalyzed Oxygenation. Issue 3 (26th November 2013) - Nawratil, Swantje; Grypioti, Maria; Menendez, Christophe; Mallet‐Ladeira, Sonia; Lherbet, Christian; Baltas, Michel
Abstract: Benzyltriazoles have been catalytically oxidized by using CuI and tert ‐butyl hydroperoxide to yield phenyl(1 H ‐1, 2, 3‐triazol‐4‐yl)methanone derivatives in good yields at room temperature. Abstract : Benzyltriazoles have been catalytically oxidized by using CuI and tert ‐butyl hydroperoxide to yield phenyl(1 H ‐1, 2, 3‐triazol‐4‐yl)methanone derivatives in good yields at room temperature.